Drug-nutrient interactions of antihypertensives and antidiabetics prescribed at Alcides Carneiro University Hospital (Research, Society and Development, 2020)
Patients affected by hypertension and/or diabetes mellitus may be susceptible to drug-nutrient interactions due to frequent use of medications and possible pharmacological associations. Therefore, the aim of this study was to investigate the possible drug-nutrient interactions – and their respective mechanisms of action – of antihypertensives and antidiabetics prescribed at the Alcides Carneiro University Hospital, as well as to present recommendations that assist health professionals and users in the proper management of these interactions. Therefore, a descriptive exploratory study of qualitative approach was carried out, using the technique of direct observation; which consisted of a contact with the pharmaceutical sector of the hospital to obtain information related to the prescribed drugs, and a subsequent survey in scientific articles, books and electronic bularia to identify their possible interactions with food in general, in addition to the mechanisms that permeate them. Among the total of 18 drugs prescribed for hypertension, important interactions were found for 83.3% (n=15), while of the 5 drugs for the treatment of diabetes, 100% (n=5) demonstrated to have interactions with some food/nutrient. The results contributed to further scientific clarification about the potential interaction of food/nutrients with antihypertensives and antidiabetics and will serve as a search tool for health professionals, especially HUAC, and other stakeholders.